Symbolism and Cultural Economy: Ngepan Skrang as Heritage and Identity of the Iban Community in Sarawak - Alexander, Chelum; Rafeah, Legino; Asrul Asshadi, Mohamad Morni; Siti Shahida, Kamel (2025)
Ngepan Skrang, the traditional Iban attire adorned with antique coins, functions not only as personal clothing but also as a symbol of cultural heritage and the collective identity of the Iban community in Sarawak. This study examines the symbolic meanings and the cultural-economic roles embodied in Ngepan Skrang, highlighting its position as an artifact that connects aesthetic, historical, and socioeconomic values. Employing a multidisciplinary approach that includes historical analysis, ethnographic study, and material culture observation, this research uncovers the narratives, values, and craftsmanship underlying this traditional attire. The findings reveal that Ngepan Skrang not only reflects the uniqueness of Iban culture but also plays a vital role in preserving collective memory, constructing identity, and strengthening the cultural economy of the Iban community in Sarawak.